Analisis sifat kuat tarik dan tekan kayu malapoga yang di rendam dengan air kondensasi - Faisal Sukardi; Awal Syahrani; Anjar Asmara (Badan Kerja Sama Teknik Mesin Indonesia, 2018)
Malapoga wood is one of the endemic wood that grows in tropical regions like in Central Sulawesi Province. The purpose of this research is to find out tensile strength and press malapoga wood which is soaked with condensation water. The result of tensile strength test and the compressive strength of malapoga wood with the variation of immersion happened the increase of tensile strength and compressive strength along with the duration of immersion. The longer the immersion time the value of tensile strength and compressive strength increases. The highest value of tensile strength and compressive strength is on soaking for 10 weeks with a tensile strength value of 59,520 MPa and its compressive strength is 29,775 MPa. While the value of tensile strength and the lowest pressure is on the specimen without immersion (raw material) with a tensile strength of 56.040 MPa and a compressive strength of 24.985MPa. Increased tensile strength of 5.84% and an increase in compressive strength of 16.08% of raw material.